Peripherally diketopyrrolopyrrole-functionalized dendritic oligothiophenes – synthesis, molecular structure, properties and applications. Issue 9 (19th January 2017) - Gao, Wei; Luo, Qun; Wang, Junkai; Lin, Yi; Tang, Changquan; Dou, Junyan; Tan, Hongwei; Zheng, Qingdong; Ma, Chang-Qi; Cui, Zheng
Abstract : Structure defined DPP functionalized conjugated thiophene dendrimers with a narrow optical band gap and a high TPA cross section are reported. Abstract : Three-dimensional π-conjugated dendrimers are a class of structure defined macromolecules for use in organic electronics. Herein, a new family of dendritic oligothiophenes (DOT-p-DPPs) that are functionalized with the diketopyrrolopyrrole group at the periphery were synthesized by a precise stepwise approach. The chemical structure and the monodisperse nature of these DOT-p-DPPs were confirmed by NMR, MALDI-TOF MS, HR MS, and GPC measurements. UV-vis absorption and fluorescence spectra and cyclic voltammetry data of these compounds were also measured. Small band gaps (∼1.8 eV) and almost identical HOMO/LUMO energy levels (−5.2/−3.5 eV) were measured for these DOT-p-DPPs independent of the molecular size. However, the molecular molar extinction coefficient ( ε ) of DOT-p-DPPs was found to be linearly correlated with the number of terminal DPP units, and a high ε of 3.6 × 10 5 cm −1 L mol −1 was measured for the bigger molecules. These results in combination with theoretical calculation results confirm that the frontier molecular orbitals are mostly localized over the peripheral DPP units. The applications of DOT-p-DPPs in organic solar cells as the electron donor are presented. However, unfavorable nanophase separation and lower DOT-p-DPP content in the blended films led to poor device performance. The two photon absorption cross section of these DPP decorated dendrimers was measured, and high cross section values of over 2000 GM were measured for these dendritic molecules, among which the G1 dendrimer6T-p-DPP with a high TPA cross section value close to 7000 GM was achieved.